华教观的差异 ：马来西亚国民中学与华文独立中学比较研究 = Difference views Of Chinese education in Malaysia national schools and Chinese private schools - Ng, Jun Xiong (2018)
国民团结不利。即便是华人民族内部，对于“华人性”和华教的观点也不全然相同。由于华文独中一直以来被视为“中学华文教育正统”，因此独中生普遍上相对国中生会有一股“文化优越感”。尽管这种优越感并不一定通过贬低他者而表现出来，但也导致独中师生对于国中华文教育缺乏客观认识而容易产生误解。本文希望通过比较独中及国中两者的教学环境、华文课本及课纲，检视其中的共同点及差异，以得出两个群体间华教观产生分歧的原因。 Chinese education in Malaysia not only has a long history, but also has been developed and restructured into a complete education system, from primary level to tertiary level. The transformation is definitely not an easy task given that Malaysia is a multiracial country with Chinese being the minority race. However, Chinese education issues are not always purely education issues, but they also relate to politics, racial harmony, nationalism as well as the multiracial nature of Malaysia. Although Chinese education and national education system exist side-by-side in Malaysia, their coexistence has not always been harmonious. Chinese education issues are often related to Malay culture issues as the Chinese educated community thinks that mother tongue education is a human right for everybody, but Malay politicians opine that mother tongue education is threatening national unity among races in Malaysia. On the other hand, there is a debate about “What is Chinese?” and “What is Chinese Education” within the Chinese society. Some think that Malaysian Chinese must master a high proficiency of Chinese language, while others believe that it is not necessary. Chinese private schools are often treated as the orthodox of Chinese education, due to the use of Chinese language as their teaching medium and their historical origin. In addition, Chinese private schools have longer Chinese classroom hours and apparently higher quality and quantity of Chinese language materials as compared to the national schools’ Chinese classes. Therefore, Chinese private schools are often regarded as more superior to the national schools’ Chinese classes, as the latter is seen as a marginal focus in the Chinese education system and national education system. Although this superiority may not necessarily be formed through discrimination of the other party, it may cause both sides to have stigma or wrong perceptions about each other. Therefore, this article seeks to uncover the reason behind the different perceptions of “Chineseness” and Chinese education between the private schools and national schools, by comparing their teaching environment, textbooks and teaching philosophy.